The Legal Background and Status of Macedonia as a Non-Nuclear-Weapon State (NNWS) in International Relations - Stojchevska, Stefani (Acta Universitatis Danubius. Juridica, 2024)
The objective of this research paper is to analyze the legal background and status of Macedonia as a non-nuclear-weapon state in global nuclear-related affairs due to recent geopolitical fluctuations in arms control and disarmament. Prior work addressing this research topic is relatively scarce apart from loosely related government reports and academic papers. The research approach includes legal commentaries on Macedonia’s nuclear-related legislation and policy, as well as ratified international treaties. Results derived from this research imply that Macedonia must reinforce its position in nuclear politics and its potential use of nuclear energy, which should be of further interest to scholars and researchers working in this field of study. The value of this paper lies in its distinctive research topic for Macedonian academic literature being comprehensively analyzed to further reach international interests.